RELATION BETWEEN TEACHING AND EDUCATION - Lipsy, Mary (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Choosing a school subject to specialize in is largely a personal choice that is going to be dependent on your interests as an individual and your strengths as a teacher. In addition, the school subjects that you end up teaching in the classroom may vary from year to year, so it’s important to have a broad education as well as several specialties. When you start thinking about what you want to teach, you should consider the subjects you enjoy and are passionate about and the age and grade level of the students you plan to work with, as well as in-demand subjects. While you may be called upon to teach various subjects, these are all considerations and can impact your career path as a teacher.